Comparative Efficiency of Mineral, Chelated and Nano Forms of Zinc and Iron for Improvement of Zinc and Iron in Chickpea (Cicer arietinum L.) through Biofortification - Salwinder Singh Dhaliwal; Vivek Sharma; Arvind Kumar Shukla; Vibha Verma; Sanjib Kumar Behera; Prabhjot Singh; Saqer S. Alotaibi; Ahmed Gaber; Akbar Hossain (Agronomy, 2021)
Nanoparticles (NPs), due to their tailored properties, serve as potential sources of nutrients for the biofortification of edible grains. Chickpeas are a valued legume crop, widely consumed in developing countries. Thus, to improve the Zn and Fe content in chickpeas, a two-year study was conducted to examine the potential of the foliar application of mineral (0.5% Zn and Fe), chelated (0.3% Zn and Fe) and nanoforms (0.5% ZFN) of fertilizers to enhance Zn and Fe content in chickpea. The foliar application of 0.5% ZnO NPs + 0.5% Fe2O3 NPs (ZFN) at the pre-flowering stage showed the highest potential to increase grain yield, Zn and Fe content and their uptake as a single foliar application of nano-fertilizers showed comparable results to two foliar applications of mineral and chelated forms. The grain and straw yield (14.07 and 33.04 q ha−1, respectively) under ZFN treatment was significantly higher over the control (9.20 and 27.49 q ha−1, respectively). A similar trend was observed for Zn and Fe content in grain (42.29 and 86.51 mg kg−1, respectively). For nutrient uptake, ZFN treatment showed the highest uptake of Zn and Fe in grain (604.49 and 1226.22 g ha−1, respectively) and straw (729.55 and 9184.67 g ha−1, respectively). Thus, nano-fertilizers, due to their altered structural properties, demonstrated higher translocation over the mineral and chelated forms of nutrient fertilizers and thus improved yield and nutrient content to a greater extent. Thus, the foliar application of 0.5% ZnO NPs + 0.5% Fe2O3 NPs may prove to be a feasible option for the enrichment of chickpeas with Zn and Fe to ameliorate malnutrition in burgeoning human populations.